SISTEM PENGETAHUAN KEBUDAYAAN MASYARAKAT DIENG DALAM MEMAKNAI SAKIT PADA BOCAH GEMBEL (STUDI KASUS DI DUSUN SIGEDANG, DESA SIGEDANG, KECAMATAN KEJAJAR, KABUPATEN WONOSOBO) - Rini Iswari, Unik Dian Cahyawati Kuncoro Bayu Prasetyo (Faculty of Social Science, Universitas Negeri Semarang, 2015)
This study aims to describe the system of knowledge in society Dieng of understanding of the disease on child beggars in the village Sigedang, District Kejajar Wonosobo regency. Secondly to find out how parents treat bocah gembel when experiencing pain. This research is descriptive qualitative interviews and documentation to collect data. The results showed if communities Sigedang village has its own system of knowledge of understanding of pain experienced by the child beggars. The second result is parents treat bocah gembel differently when child beggars beggars belief pain associated with tangled hair with no pain associated with tangled hair.